Prognostic markers of urinary bladder cancer lymphatic spread - V. N. Pavlov; A. A. Izmailov; S. M. Izmailova; T. V. Viktorova; M. F. Urmantsev (Бюллетень сибирской медицины)
Treatment results (2005—2009) for patients with invasive (N=104) urinary bladder carcinoma were analyzed. Molecular genetic analysis of cytochrome gene P450 polymorphous locus carried out: CYP1А1 (A2455G), СYP1A2 (T-2464delT), Glutathione S-transferase: GSTM1 (del), GSTP1 (A313G); DNA reparation: XRCC1 (G28152A) for patients with invasive urine bladder carcinoma with and without lymphogenic metastases was carried out. Genotypes associated with lyphogenic metastasis risk were identified.